Quantifying canine tissue stiffness change patterns using shear-wave elastography: implications for time of death estimation - Ong, Wee Kee; Leong, Sook Sam; Azman, Raja Rizal; Md Shah, Mohammad Nazri; Vijayananthan, Anushya; Lau, Seng Fong (Taylor and Francis, 2024)
This study investigates the applicability and reproducibility of shear-wave elastography (SWE) in detecting changes in tissue stiffness of canine carcasses. SWE was performed on six canines by two operators. The target organs were liver, spleen, kidney, and thigh muscles. SWE was performed ante-mortem and up to 48-hours post-mortem at specific intervals. The Mann-Whitney U-test and Spearman correlation coefficient showed insignificant correlation between gender and weight with shear-wave velocity (SWV) in ante-mortem scans. The Kruskal-Wallis H-test showed significant differences in SWV for all organs. Intraclass correlation coefficient (ICC) showed excellent correlation for all target organs except for kidneys. Pairwise comparison showed a similar SWV trend for abdominal organs. Accuracy metrics were calculated for determining the post-mortem interval using SWV values. The liver had the highest accuracy (0.69–0.83) across different post-mortem interval thresholds within the cut-off values of ≥2.0 m/s, 1.8–2.0 m/s, <1.8 m/s indicating ≤6 hours post-mortem, 12–18 hours post-mortem and >18 hours post-mortem. The spleen, kidney and thigh muscle demonstrated moderate-to-poor accuracy within the same cut-off parameters. Post-mortem SWV changes in canine solid organs, and soft tissues, particularly the liver, demonstrate a reproducible pattern, which may have value in determining the post-mortem interval.